PART B, VOLUME 2, CHAPTER 5: MICROBIALLY INDUCED SEDIMENTARY STRUCTURES (MISS) - Noffke, Nora (2022)
Fil: Noffke, Nora. Old Dominion University, Department of Ocean, Earth and Atmospheric Sciences, Norfolk, Virginia 23529, USA